ISOLATION AND DIAGNOSIS OF MYCORRHIZA FUNGUS AND USED ON PHYTOREMEDIATION FOR SOIL TREATED WITH SEWAGE SLUDGE ANDGROWTH OF MAIZE PLANT - Salman, Nariman D. (Diyala Agricultural Sciences Journal, 2018)
A pot experiment was conducted at the lath –house of the Department of Soil Sciences and Water Resources, College of Agriculture, University of Baghdad during 2013 spring season, using loamy sand texture soil to study isolation and diagnosis of mycorrhiza and sewage sludge and their effect on growth maize plant and Cd and Pb concentration. Treatments were five sewage sludge levels (0, 25, 50, 75 and 100 μg h-1) coded as (S0, S1, S2, S3 and S4) with two treatments of mycorrhiza (without inoculation, with mycorrhiza, Gloums intraradics) coded as (AM0, AM1). This study was designed according to Complete Randomized Design (CRD) in three replicates. Results showed that a diagnosis of mycorrhiza fungus for genes level and species with use PCR through conformable properties for fungus Gloums intraradics and Glomus mosseae. Results showed that an inoculated of mycorrhiza significant reduced Cd and Pb, while increase in shoot and root dry weight. Increase in accumulation rate of heavy metals (Cd and Pb) in root system, compared to shoot system, which showed rate of accumulation almost four times lower than the roots.